Pemanfaatan Website Dinas Komunikasi dan Informatika Kota Medan dalam Mewujudkan Keterbukaan Informasi Publik - Etin Indrayani; Sultan Haga Purba; Suhajar Diantoro (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2025)
This study aims to analyze the utilization of the Medan City Communication and Informatics Office website in providing public information. The research method used is descriptive qualitative, with data collection techniques that include observation, interviews, and documentation. Data processing was done using NVivo software to identify key themes in the qualitative data. The findings indicate that although the Diskominfo Medan website presents updated news, it lacks interactive menus, public service features, and community engagement. Therefore, content structure optimization, human resource development, and integration of two-way communication features are essential to achieving the goal of public information transparency.